UNDERSTANDING CRITICAL PEDAGOGY AND ITS IMPACT ON THE CONSTRUCTION OF KNOWLEDGE - Zygmantas, Janete (Acta Paedagogica Vilnensia, 2009)
This article highlights the underlying principles in the construction of knowledge drawing on the theoretical framework postulated by Critical Pedagogy. It also stresses the importance of viewing human beings as co-creators of the world by being able to integrate new knowledge into previous knowledge and, consequently, taking an active role in this process. Conversely, when humans are not able to create new knowledge under such circumstances, they remain disconnected and simply adapt to the world. Having said so, it is vital that education provide both teachers and students with the chance to (re)construct their knowledge and become Subjects of their own thinking. As a result, they will be better able to learn to learn.